Hypopharyngeal Dedifferentiated Liposarcoma in the MDM2 Era: A Case Report and Short Review - Peter Wanes; David A. Nolte; Ghassan A. Tranesh (Case Reports in Pathology)
Pharyngeal liposarcomas are very rare; still more rare are dedifferentiated liposarcomas in the pharynx. An 82-year-old man presented with dysphagia, voice changes, weight loss, nasal regurgitation of liquids, and coughing spells. A 3.5 cm mass was identified in the hypopharynx. The mass was biopsied and diagnosed as a benign fibroepithelial polyp. Continued symptoms and airway obstruction prompted a pharyngectomy, and the mass was then diagnosed as dedifferentiated liposarcoma. Due to infrequency and subtle histological findings, liposarcomas of the head and neck can be misdiagnosed and recur.